The rate of visual field loss in untreated primary open angle glaucoma. - Jay, J L (1993)
The mean rate of visual field loss in untreated primary open angle glaucoma was estimated by comparing the mean age at presentation of patients with early relative visual field loss with the mean age of those who presented with absolute field loss within five degrees of fixation. Analysis of the records of 177 patients indicated that the rate of field loss was related to the level of untreated intraocular pressure. For pressures of 21 to 25 mm Hg, untreated disease is likely to progress from early field changes to end stage in an average of 14.4 years. The same interval for pressures of 25 to 30 mm Hg was 6.5 years and for pressures over 30 mm Hg, 2.9 years. For untreated disease at pressures over 25 mm Hg the interval is estimated at 3.6 years and this is much shorter than the estimated period of 10 years under imperfect treatment and 38 years under optimum treatment identified in a prospective clinical trial of early trabeculectomy in patients with similar intraocular pressures at diagnosis.